On ’Opuntia spinulifera’ and ’O. streptacantha’ (Cactaceae), new to Spain, and the status of ’O. huajuapensis’ in that country - Verloove, Filip; Sanchez Gullon, Enrique; Guiggi, Alex (Mediterranean Botany, 2020)
Opuntia spinulifera and O. streptacantha are reported for the first time from Spain. Both are more or less naturalized in scattered localities in Ayamonte (province of Huelva, SW Spain) where they were previously confused with O. huajuapensis. Claims of the latter from other Spanish regions are shown to be also erroneous. These three species, as well as O. leucotricha, have apparently been confused. Distinguishing features useful for their separation are discussed and the species that are present in Spain are illustrated.